2022
DOI: 10.15547/bjvm.2336
|View full text |Cite
|
Sign up to set email alerts
|

Tongue rolling stereotypy in cattle – etiological, epidemiological and clinical investigations

Abstract: The present studies were carried out to establish the causes for appearance, prevalence, age- and sex-related features, the frequency and 24-hour pattern of clinical signs accompanying the tongue rolling stereotypy in cattle. The animals were distributed in 2 groups: group I (n=1055) – control animals that did not demonstrate the tongue play orosthenic syndrome and group II (n=48) – cattle manifesting this stereotypy. Both groups were uniform with regard to age, breed, body condition and sex. They were placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…The authors assume that tongue rolling has a calming function that reduces the activity of the sympathetic nervous system in stressful situations. In contrast, Binev (2022) found increased values of vital parameters (body temperature, heart rate, respiratory rate, ruminal motility rate) in cows performing oral stereotypies compared with a control group, but these findings were not significant. Changes in animal routine, such as avoiding milking by an induced power cut in the automatic milking system, resulted in a significant increase in tongue rolling in dairy cows (Graeff et al, 2017).…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…The authors assume that tongue rolling has a calming function that reduces the activity of the sympathetic nervous system in stressful situations. In contrast, Binev (2022) found increased values of vital parameters (body temperature, heart rate, respiratory rate, ruminal motility rate) in cows performing oral stereotypies compared with a control group, but these findings were not significant. Changes in animal routine, such as avoiding milking by an induced power cut in the automatic milking system, resulted in a significant increase in tongue rolling in dairy cows (Graeff et al, 2017).…”
contrasting
confidence: 60%
“…investigation 3 out of 21 observed cows showed a combination of two stereotypic behaviors. This does not seem to be unusual, because Binev (2022) found in 6 out of 48 cows a combination of stereotypic behavior as well. Independent of whether the cows had access to the pasture or not the average LP ranged between 6.15 s and 110.15 s. Eleven of the 21 observed cows (52.4%) had an average LP of more than 30 s. These findings disagree with the results of Binev ( 2022) who found 92% of the examined cows performing stereotypic behavior less than 30 s. In this study, the cows of both investigated farms showed stereotypic behaviors consisting of tongue playing, licking of the barn equipment, and a combination of both behaviors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Enrichments allowing for oral manipulation, specifically ropes, are provided to cattle when they may be deprived from fulfilling their natural oral behaviours of suckling and/or grazing, but mature cattle appear to interact with these ropes less; dairy: [ 9 , 10 ]; beef: [ 14 , 49 , 50 ]. Bark stripping is an oral stereotype seen in cattle [ 51 , 52 ], and is associated with a lack of foraging [ 16 , 53 ], some dietary deficiencies such as lack of manganese or fibre [ 54 , 55 , 56 ], or social learning [ 51 ]. Considering oral behaviours were mainly concentrated on different enrichments between cohorts (woodchip vs. stump), it is possible that this was a socially learnt behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…When cattle are in a feedlot environment or on thick improved pastures (i.e., grazing lands not used for cropping), eating time is reduced and replaced with other oral behaviours when compared to cattle in paddocks with low pasture availability [ 15 ]. Although some oral behaviours such as tongue rolling may be defined as stereotypic behaviours [ 16 ], other exploratory behaviours may be rewarding to the cattle. Beneficial oral behaviours could be encouraged in both paddock-based and intensive systems through the provision of objects such as ropes, which can be chewed or suckled.…”
Section: Introductionmentioning
confidence: 99%